2006
DOI: 10.1039/b518288c
|View full text |Cite
|
Sign up to set email alerts
|

ESI-MS study on the aldol reaction catalyzed by l-proline

Abstract: The aldol reaction catalyzed by L-proline has been monitored and the accepted mechanism confirmed by intercepting and characterizing, for the first time, all the proposed intermediates by ESI-MS/MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
0
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 25 publications
4
65
0
6
Order By: Relevance
“…5) reveals the following facts: the oxazolidinones derived from aldehydes are more stable with the substituent at C(2) in the exo-position, in nonsymmetrical ketone derivatives the larger substituent will prefer to reside in the exoposition, and in oxazolidinones derived from symmetrical ketones the substituent in the exo-position is less sterically hindered (Fig. 5, a and b) 42 ). Furthermore, in the spirocyclic cyclohexanone-derived oxazolidinone 8, the conformer with axial O-atom and equatorial N-atom has to be assumed to be more stable than the conformer with the two heteroatoms reversed 43 ) (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5) reveals the following facts: the oxazolidinones derived from aldehydes are more stable with the substituent at C(2) in the exo-position, in nonsymmetrical ketone derivatives the larger substituent will prefer to reside in the exoposition, and in oxazolidinones derived from symmetrical ketones the substituent in the exo-position is less sterically hindered (Fig. 5, a and b) 42 ). Furthermore, in the spirocyclic cyclohexanone-derived oxazolidinone 8, the conformer with axial O-atom and equatorial N-atom has to be assumed to be more stable than the conformer with the two heteroatoms reversed 43 ) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…For a dissociative ring-opening of an oxazolidinone to a zwitterionic iminium carboxylate (Fig. 5, d), a process that formally does not follow a 42 ) All pivalaldehyde derivatives have exclusively exo-configuration [16 -19] [55], so has the chloral derivative of proline [7]. In oxazolidinones derived from aldehydes RCHO with smaller R groups, NMR-detectable amounts of a minor diastereoisomer have been reported ([8] and hitherto unpublished results by W. Prikoszovich, B. Linder, Novartis Pharma AG, Basel).…”
Section: Methodsmentioning
confidence: 99%
“…Although aldehyde-derived "Seebach oxazolidinones" (15)(16)(17) have long been known, their ketone analogues have only recently been detected and characterized by us (14) and later isolated also by Seebach et al (18). Interestingly, the condensation product of acetone and proline has also been detected by Marquez and Metzger using mass spectrometry (19). In light of our previous careful NMR-spectroscopic characterization of this adduct as an oxazolidinone (14), their assignment as an enamine appears to be questionable.…”
mentioning
confidence: 97%
“…Furthermore, based on List's studies [46] we have also observed the presence of a linear relationship between the enantioselectivity of the catalyst and the observed enantioselectivity of the aldol product, thus supporting the involvement of only one molecule of the prolinethioamide in the transition state [18]. For the L-proline catalyzed aldol reaction all assumed intermediates involved were characterized by ESI-MS study [47]. While using the 1 H NMR technique, the formation of assumed iminium ion was observed in the thioamide catalyzed reaction [30].…”
Section: Mechanism Of the Aldol Reaction Catalyzed By Prolinamide Dermentioning
confidence: 99%